2010
DOI: 10.1101/cshperspect.a001131
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and Function of the Invertebrate p53 Superfamily

Abstract: The origin of the p53 superfamily predates animal evolution and first appears in unicellular Flagellates. Invertebrate p53 superfamily members appear to have a p63-like domain structure, which seems to be evolutionarily ancient. The radiation into p53, p63, and p73 proteins is a vertebrate invention. In invertebrate models amenable to genetic analysis p53 superfamily members mainly act in apoptosis regulation in response to genotoxic agents and do not have overt developmental functions. We summarize the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 79 publications
(128 reference statements)
3
89
0
1
Order By: Relevance
“…Recent findings also implicate p53 in the regulation of lifespan. Invertebrates such as worms and flies do not develop cancer upon deletion of p53 (Rutkowski et al, 2011). Nevertheless, p53 deficiency broadly affects development, metabolism, cell death, the response to genotoxic stress and the overall fitness of the organism, which may account for the impact of p53 on life expectancy ( Fig.…”
Section: P53mentioning
confidence: 99%
“…Recent findings also implicate p53 in the regulation of lifespan. Invertebrates such as worms and flies do not develop cancer upon deletion of p53 (Rutkowski et al, 2011). Nevertheless, p53 deficiency broadly affects development, metabolism, cell death, the response to genotoxic stress and the overall fitness of the organism, which may account for the impact of p53 on life expectancy ( Fig.…”
Section: P53mentioning
confidence: 99%
“…The idea that the C. elegans germline recapitulates apoptotic mechanisms found in mammalian cells was reinforced by the identi fi cation of a p53 homolog in the worm genome, cep-1 ( C. elegans p 53-like 1 ) (Derry et al 2001 ;Schumacher et al 2001 ; for recent reviews, see Rutkowski et al 2010 ) . The identity of cep-1 remained elusive despite the C. elegans genome sequence being known for several years, based on its low level of sequence conservation, which is essentially restricted to its DNA-binding domain.…”
Section: Pathways Leading To Dna Damage-induced Apoptosismentioning
confidence: 99%
“…The identity of cep-1 remained elusive despite the C. elegans genome sequence being known for several years, based on its low level of sequence conservation, which is essentially restricted to its DNA-binding domain. In mammals, the p53 family of transcription factors includes p63 and p73 and phylogenetic analysis that included many invertebrate species indicated that the radiation into those three groups occurred during vertebrate evolution (Rutkowski et al 2010 ) . However, it was recently shown that placozoans, which are very simple animals, and ticks have Mdm2-like proteins and p53 family members much more related to mammalian p53 (Lane et al 2010a, b ) .…”
Section: Pathways Leading To Dna Damage-induced Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with findings that these regulators evolved first in Choanozoans from the Opisthokonta group (Rutkowski et al. 2010). p21 and pRb are also absent in Giardia .…”
Section: Resultsmentioning
confidence: 99%